2014
DOI: 10.1136/bcr-2014-205372
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid reanimation, neurotisation, and transplantation of the cornea in a patient with facial palsy

Abstract: Patients affected by facial palsy suffer from failure to fully close the eyelids; the resulting eye exposure can lead to dry eye syndrome, loss of epithelial integrity, corneal ulceration and infections. Corneal anaesthesia exacerbates risk of corneal damage in these patients. Eyelid paralysis-associated corneal lesions may induce severe visual impairment, for which the ideal treatment is corneal transplantation, a procedure contraindicated in patients with corneal sensitivity and inadequate eyelid closure. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 5 publications
1
25
0
1
Order By: Relevance
“…23,24 Lateral and medial canthoplasties, canthopexy, and ectropion correction are commonly required.…”
Section: Closure Of the Eyelidsmentioning
confidence: 99%
“…23,24 Lateral and medial canthoplasties, canthopexy, and ectropion correction are commonly required.…”
Section: Closure Of the Eyelidsmentioning
confidence: 99%
“…Allevi et al 53 reported a case in 2014 of a patient who had previously undergone facial motor reanimation followed by direct corneal neurotisation using the technique described by Terzis et al 48. The authors transferred the contralateral supraorbital and supratrochlear nerves to four perilimbal cardinal points around the affected cornea by the above technique.…”
Section: Introductionmentioning
confidence: 99%
“…Interpositional nerve graft techniques coapted to a healthy donor nerve: A–F, Elbaz et al ,49 Bains et al ,50 Weis et al ,59 Fung et al 89; and direct nerve transfer (G, Terzis et al ,48 Allevi et al ,53 Ting et al ,57 Leyngold et al— supraorbital nerve only56; H, Jacinto et al 54; I, Professor Gennaro (personal communication, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques of corneal neurotization have been described. [21][22][23][24][25][26] Neurotization was performed in our model by using the contralateral ION via two autografts, similar to the technique described by Elbaz et al 21 The contralateral ION was used, as it is robust in the rat, and a contralateral donor permitted the confirmation with retrograde labeling that reinnervation of the cornea was derived from the contralateral donor nerve. Because each graft measured approximately 30 mm in length, the surgical procedure to place the grafts was performed prior to stereotactic ablation of the ophthalmomaxillary nerve.…”
Section: Discussionmentioning
confidence: 99%